Salmonella sp and Clostridium botulinum in waterfowl and sea-birds - Steiniger, F (Wildfowl, 1962)
Discussion of whether water birds may be infected by salmonellas in conditions of waters polluted by sewage and whether they spread the infection to clean waters.